Feasibility study of using IRT-T research reactor for BNCT applications; Applied Radiation and Isotopes; Vol. 166 - Anikin M. N. Mikhail Nikolaevich; Lebedev I. I. Ivan Igorevich; Naymushin A. G. Artem Georgievich; Smolnikov N. V. Nikita Viktorovich (2020, 2020)
Title screen